Ideologizacja kultury wiejskiej na przykładzie biblioteki w Czerwieńsku w powiecie zielonogórskim w latach 1949-1956 = The Ideologization of Rural Culture as Exemplified by the Library in Czerwieńsk, Zielona Góra County, 1949-1956 - Koteluk, Daniel (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The text fragment describes the functioning of the public library in Czerwieńsk in the post-war period, particularly during the Stalinist era and the mid-1950s. The number of readers was relatively small ? about 80 in 1948 and around 216 in 1956, although the number of active users was lower. An additional problem was that books were often borrowed by unregistered readers and not returned. The head librarian attempted to encourage local residents to use the library and participate in cultural activities, but these efforts were mostly met with indifference.Readers showed little interest in agricultural, technical, and ideological literature promoted by the authorities. Instead, they preferred classical Polish literature, including works by Żeromski, Kraszewski, Sienkiewicz, Prus, and Konopnicka, as well as some Russian authors such as Tolstoy, Turgenev, and Sholokhov. Authorities tried to increase readership and promote ideologically appropriate literature through administrative measures, but the library suffered from poor funding and these initiatives brought limited results.Many Western authors, especially writers of crime and popular fiction, were absent from the library collections. Young people, however, eagerly read pre-war westerns and adventure novels that circulated unofficially. The authorities attempted to restrict such literature through the actions of the security apparatus, teachers, and youth organizations. The fragment highlights the clear tension between communist cultural policy and the actual reading interests of rural residents.
Keywords: biblioteki miejskie; Czerwieńsk; czytelnictwo; wieś; PRL; polityka kulturalna; propaganda komunistyczna; mieszkańcy wsi; Związek Młodzieży Polskiej (ZMP); cenzura; ideologizacja; literatura; city libraries; reading; village; cultural policy; communist propaganda; censorship; ideologization; literature; Union of Polish Youth (ZMP)